2018
DOI: 10.1177/2324709618790605
|View full text |Cite
|
Sign up to set email alerts
|

Intramural Ectopic Pregnancy Following Myomectomy

Abstract: Intramural pregnancy is a rare form of ectopic pregnancy with early diagnosis essential for prevention of severe hemorrhage and uterine rupture. We report a rare case of an intramural ectopic pregnancy at 12 weeks gestation in a woman 1 year post open myomectomy. Both transvaginal ultrasound and magnetic resonance imaging were utilized as diagnostic aids in this case. The rare nature of this clinical scenario and lack of guidelines for management made clinical decision making difficult. Due to the size and loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 15 publications
0
21
0
1
Order By: Relevance
“…To the best of our knowledge, only seven cases diagnosed with MSP have been previously reported. [2][3][4][5][6][7][8] Of the total number of eight cases including our case, two were the result of spontaneous conception and six of in vitro fertilization. Among the patients, the age ranged from 27 to 35 years, and all cases were diagnosed on the basis of ultrasonic testing, with or without MRI/computed tomography.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…To the best of our knowledge, only seven cases diagnosed with MSP have been previously reported. [2][3][4][5][6][7][8] Of the total number of eight cases including our case, two were the result of spontaneous conception and six of in vitro fertilization. Among the patients, the age ranged from 27 to 35 years, and all cases were diagnosed on the basis of ultrasonic testing, with or without MRI/computed tomography.…”
Section: Discussionmentioning
confidence: 78%
“…After reviewing all cases and published English literature, we found seven MSP cases. [2][3][4][5][6][7][8] The clinical findings for each case are listed in Table 1.…”
Section: Case Reportmentioning
confidence: 99%
“…However, each patient is in different situation and cases associated with ART published so far are rare [10][11][12]. The etiological factors of intramyometrial pregnancy include previous uterine trauma, like hysteromyomectomy [11,13], previous curettage [14][15][16][17], cesarean delivery [6], salpingectomy [18], manual removal of placenta, and especially IVF-ET procedure, resulting in a microscopic sinus tract within the endometrium. Embryo may implant into the myometrium with ectopic endometrial tissues during endometriosis development [19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…Only two cases in literature have been reported that gestation continued without rupture until over 30 weeks' gestation with neonatal survival [23,25]. Delayed diagnosis leads to uterine rupture, hysterectomy, maternal hemoperitoneum, hypovolemic shock, and other life threatening consequences [13]. Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation